Toxic leadership behaviour of nurse managers and turnover intentions: the mediating role of job satisfaction - Adelaide Maria Ansah Ofei; Collins Atta Poku; Yennuten Paarima; Theresa Barnes; Atswei Adzo Kwashie (BMC, 2023)
Abstract Introduction Globally, hospitals are confronted with major challenges of turnover of nurses. Knowledge of the factors that account for the turnover of nurses will aid in creating strategies that will enhance nurse managers' leadership behaviour and job satisfaction to reduce turnover. The study, therefore, investigated the mediating role of job satisfaction on toxic leadership and turnover intentions of nurses. Methods A multi-centre cross-sectional study was undertaken to assess 943 nurses using the Toxic-leadership Behaviour of Nurse Managers scale, Minnesota Satisfaction Questionnaire and Turnover Intention scale. Descriptive statistics was used to assess the prevalence of toxic leadership, job satisfaction and turnover and Pearson's correlation examined the relationships between the variables. Hayes' PROCESS macro approach of mediation was used to determine the effect of toxic leadership behaviour on the turnover intention on the possible influence of job satisfaction. Results The response rate for the study was 76.0%. Mean scores for turnover intentions and toxic leadership behaviour were 3.71 and 2.42 respectively. Nurses who work with toxic managers showed a higher propensity to leave their jobs. Job satisfaction acted as a mediator between the toxic leadership practices of managers and turnover intentions. The total effect of toxic leadership behaviour on turnover intention comprised its direct effect (β = 0.238, SE = 0.017, 95% CI [0.205, 0.271]) and its indirect effect (β = -0.020, SE = 0.017). Conclusions Job satisfaction acted as a mediating factor for toxic leadership behaviour and nurses' turnover intentions. As part of nurse retention initiatives, avoiding toxic leadership behaviours will be the ultimate agenda. Nurse administrators should recognize the value of excellent leadership and develop a structured training programme through the use of evidence-based professional development plans for nurse managers.